Sensitivity behavior of nanostructured zinc oxide based gas sensor fabricated by immersion method / Siti Shafura A Karim - A Karim, Siti Shafura (2018)
This study aimed to fabricate nanostructured zinc oxide (ZnO) based metalsemiconductor-metal (MSM) gas sensor by immersion method. Three stages of method were employed to fabricate nanostructured ZnO based MSM gas sensor which are: (1) preparation of ZnO nano-template by spin-coating method, (2) preparation of nanostructured ZnO on deposited ZnO nano-template layer by immersion method and (3) fabrication of nanostructured ZnO based MSM gas sensor. For preparation of ZnO nano-template by spin-coating method, both effects of multilayer coating (1 to 9 layers) and annealing temperature (350 to 500°C) of ZnO nano-template were determined. The optimised properties of deposited ZnO nano-template was further employed as a seed layer to grow nanostructured ZnO by immersion method. For preparation of nanostructured ZnO on deposited ZnO nano-template layer by immersion method, effect of molarity (0.02 to 0.10 M) and effect of n-type dopant (Sn) concentration (0.2 to 1.0 at.%) on nanostructured ZnO were evaluated. Field emission scanning electron microscope (FESEM), energy dispersive X-ray (EDS), atomic force microscopy (AFM) and X-ray diffraction (XRD) were employed to characterise the structural properties of deposited samples whereby UV-Vis-NIR spectrophotometer was used for the optical properties determination. The electrical properties were measured using current-voltage (I-V) measurement system (Keithley 2400). Next, gold (Au) was deposited on the nanostructured ZnO as an electrode for the fabrication of nanostructured ZnO based MSM gas sensor. The entire samples were characterised to determine their response and recovery time as well as the sensitivity. The sensitivity behavior of the fabricated samples were determined to detect 20 seem of methane (CH4) gas at operating temperature of 150°C. In preparation of ZnO nano-template by spin-coating method, the results revealed that 5 layers demonstrated a high uniformity with no crack and high electrical conductivity (l.lxlO"3 S/cm). Additionally, 500°C has emerged as an optimum temperature upon increment of annealing temperatures. During preparation of nanostructured ZnO on deposited ZnO nano-template layer by immersion method, unique nanostructure (flake-like morphologies) was observed upon the study of molarity effect on nanostructured ZnO (0.02-0.10 M). The electrical conductivity was obtained around 10"3 S/cm, which is comparable to previous reported studies. The optimum concentration at 0.06 M has exhibited a good uniformity with low roughness and the highest conductivity of 3.3>